2009
DOI: 10.1017/s0952523809990186
|View full text |Cite
|
Sign up to set email alerts
|

Rod bipolar cells in the retina of the capuchin monkey (Cebus apella): Characterization and distribution

Abstract: Rod bipolar cells in Cebus apella monkey retina were identified by an antibody against the alpha isoform of protein kinase C (PKCalpha), which has been shown to selectively identify rod bipolars in two other primates and various mammals. Vertical sections were used to confirm the identity of these cells by their characteristic morphology of dendrites and axons. Their topographic distribution was assessed in horizontal sections; counts taken along the dorsal, ventral, nasal, and temporal quadrants. The density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
(111 reference statements)
2
6
0
Order By: Relevance
“…In macaque, the peak rod bipolar density is about 13,000 cells/mm 2 (Grünert and Martin, ), and the peak rod density is 120,000 rods/mm 2 (Packer et al, ). The ratio of rods to rod bipolar cells in both species remains relatively constant at 8:1 and 13:1, respectively, across the retina, and similar values have been obtained in the capuchin monkey (Lameirao et al, ). Thus in primate, as in other species, the overall rod bipolar density across species follows the rod density, supporting the argument referred to above, that cell proportions in the inner nuclear layer reflect preserved microcircuits.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In macaque, the peak rod bipolar density is about 13,000 cells/mm 2 (Grünert and Martin, ), and the peak rod density is 120,000 rods/mm 2 (Packer et al, ). The ratio of rods to rod bipolar cells in both species remains relatively constant at 8:1 and 13:1, respectively, across the retina, and similar values have been obtained in the capuchin monkey (Lameirao et al, ). Thus in primate, as in other species, the overall rod bipolar density across species follows the rod density, supporting the argument referred to above, that cell proportions in the inner nuclear layer reflect preserved microcircuits.…”
Section: Discussionsupporting
confidence: 77%
“…The density data for all labeled cell populations except for Müller cells derived from the same retina. This is important, as cell densities between individuals of a given species may vary (Curcio and Allen, ; Curcio et al, ; Strettoi and Masland, ; Lameirao et al, ). We found that the fractions of the main cell classes (bipolar, amacrine, horizontal, and Müller cells) did not change much between the central and peripheral retina.…”
Section: Discussionmentioning
confidence: 99%
“…The following specific antibodies were used: anti-GFAP antibody for glial cells (raised in mouse; #3670S; Cell Signalling Technology; Danvers, MA, USA) (Lin et al 2013); anti-Thy1 antibody for RGCs (raised in rabbit; #MA1-21469; Thermo Fisher Scientific Inc., Waltham, MA, USA) ( Barnstable and Drager 1984;Nadal-Nicolàs et al 2009); and anti-PKCa antibody for RBCs (raised in Rabbit; #2056S; Cell Signalling Technology) Lameirão et al 2009). The specie-specific magnetic beads were as follows: goat anti-rabbit (#120-000-292) and goat anti-mouse (#120-000-288) IgG microbeads (Miltenyi Biotec).…”
Section: Rgcs Glial Cells and Rbcs Isolationmentioning
confidence: 99%
“…To date, the morphology and distribution of ganglion cells [21], [25][30], bipolar cells [31], [32], horizontal cells [33], rods, and cones [34][37] have been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%